Renewable Energy (RE) And Energy Efficiency (EE) Understanding And Awareness Among Secondary School Students And Teachers In Malaysia. - Mohd Yunus, Hashimah; Hashim, Nor Hashimah; Ghazali, Munirah; Ibrahim, Kamarul Azizi; Dinsuhaimi, Mohamad (2008)
This study was conducted to find out teachers and secondary students perceptions on their awareness and understanding of Renewable Energy (RE) and Energy Efficiency (EE). Earlier in 2003, a program on Renewable Energy (RE) and Energy Efficiency (EE) has been implemented by the Center for Education, Training and Research for Renewable Energy (RE) and Energy Efficiency (EE) (CETREE), Universiti Sains Malaysia.